Pengaruh Work Life Balance Terhadap Kinerja Karyawan Melalui Kesejahteraan Karyawan pada UMKM - Hartoyo, Hartoyo (Awatara Publisher, 2024)
This study explores the effect of work-life balance on employee performance through the mediating role of employee well-being among employees in micro, small, and medium enterprises (MSMEs) in Purwakarta, Indonesia. Using a qualitative approach, the research investigates how employees perceive and navigate the complex interactions between their personal and professional responsibilities. Five informants were purposively selected from various MSMEs and interviewed through semi-structured sessions. Thematic analysis revealed that work-life balance plays a critical role in preserving employees’ emotional and psychological resources, which directly influences their well-being and job performance. Well-being emerged as a lived and dynamic experience, deeply affected by recognition, social relationships, and individual strategies for managing stress. The findings align with the Conservation of Resources (COR) Theory, which posits that maintaining valued resources such as time, energy, and emotional support is key to preventing burnout and promoting effectiveness. Informants reported that imbalance leads to emotional exhaustion and decreased motivation, while balance enhances creativity, focus, and satisfaction. The research highlights the informal and relational nature of work in MSMEs, suggesting that even simple, empathetic interventions can significantly improve outcomes. This study contributes to the limited qualitative literature on MSMEs and offers practical insights for small business management in similar socio-cultural settings. It emphasizes the need for human-centered approaches to organizational practices.